(untitled) (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY Invasive streptococcal infections affect more than half a million patients worldwide every year and have a high lethality. Little is known about the epidemiology and microbiological characteristics of streptococcal infections in Switzerland. This case series study aims to describe the demographics, known risk factors for streptococcal skin and soft tissue infections, clinical presentations, treatment and outcomes of patients admitted to the University Hospital Zurich between 2000 and 2014 with invasive streptococcal infections caused by Streptococcus pyogenes (group A Streptococcus), Streptococcus dysgalactiae ssp. equisimilis or the Streptococcus anginosus group, as well as the microbiological characteristics of the clinical isolates. METHODS Data collected retrospectively from patients hospitalised between 2000 and 2014 with invasive streptococcal infections were analysed. M protein gene (emm) typing of the bacterial clinical isolates was carried out according to the Centers for Disease Control and Prevention guidelines. RESULTS A total of 86 patients with invasive beta-haemolytic streptococcal infections were included in this study, of which 49% presented with necrotising fasciitis. The median age was 44 years and half were female. The most common risk factor was acute skin lesions. C-reactive protein levels were significantly higher in patients with necrotising fasciitis, as were acute renal failure and distributive shock. Beta-lactam antibiotics were given to most patients, and intravenous immunoglobulins were given to 18% of patients within the first 24 hours. All patients suffering from necrotising fasciitis underwent surgery. The overall case fatality rate was 8.1% at 30 days post admission. All Group A Streptococcus strains were susceptible to penicillin and clindamycin, and we found resistance to tetracycline in 11.9% of strains. The most common emm-type isolated was emm1 (44.4%). CONCLUSIONS Invasive beta-haemolytic streptococcal infections, the most severe presentation of which is necrotising fasciitis, remain a serious clinical issue and require rapid diagnosis and treatment. This is the first representative analysis monitoring clinical and microbiological characteristics of patients with a severe invasive beta-haemolytic streptococcal infection and treated in Zurich, Switzerland. In addition to the detailed reporting of various clinical and microbiological characteristics, we show that C-reactive protein levels, acute renal failure and distributive shock were higher in the patients with necrotising fasciitis. We also found a low case fatality rate compared to other reports. The detailed clinical data and microbiological characteristics depicted in this study will lead to a better understanding of regional differences in severe invasive streptococcal infections.